THE ROLE OF PROTEOMIC ANALYSIS IN PREDICTING IVF OUTCOMES IN WOMEN WITH EMPTY FOLLICLE SYNDROME - Olimova, K.J.; Shukurov, F.I.; Jalolova, G.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. Predicting IVF outcomes in women with Empty Follicle Syndrome (EFS) is one of the relevant tasks in modern reproductive medicine. Aim. To evaluate the role of proteomic profiles in predicting in vitro fertilization (IVF) outcomes in women with empty follicle syndrome (EFS). Materials and methods. The study included 60 women with a history of empty follicle syndrome (EFS). The patients were divided into three groups: Group I consisted of 30 women of early reproductive age (18-35 years), Group II consisted of 30 women of late reproductive age (36-41 years), and the control group consisted of 30 healthy women without reproductive disorders. Results. Proteomic analysis revealed significant changes in the levels of proteins associated with oxidative stress, inflammation, and apoptosis. In particular, women in Group I showed increased levels of Caspase-3 and IL-6, indicating increased oxidative stress and inflammatory processes. Decreased levels of anti-apoptotic proteins, such as Bcl-2 and Survivin-2B, in this group may indicate increased cell death, negatively affecting oocyte quality and IVF success. Women in Group II showed changes associated with aging processes, including increased levels of ApoA-1 and fibronectin, as well as increased levels of Caspase-3 and IL-8. Conclusion. The study results showed that proteomic profiles can serve as reliable biomarkers for predicting IVF success in women with EFS. The identified protein markers associated with inflammation, oxidative stress, and apoptosis indicate possible mechanisms of EFS pathogenesis and can be used to develop new therapeutic strategies. Thus, the obtained data emphasize the importance of an individualized approach to treating patients with EFS, taking into account the age and biochemical characteristics of each woman, which may increase the likelihood of successful IVF outcomes.